Balanced scorecard step by step - Niven, Paul R (Wiley, 2002)
Includes bibliographical references and index; Performance Measurement And The Need For A Balanced Scorecard -- The Balanced Scorecard As An Enduring Management Tool -- Getting Started -- Mission, Values, Vision, and Strategy -- Developing Performance Objectives and Measures -- Finalizing Measures and Developing Cause and Effect Linkages -- Setting Targets and Prioritizing Initiatives -- Cascading the Balanced Scorecard to Build Organizational Alignment -- Using the Balanced Scorecard to Strategically Allocate Resources -- Linking Rewards to Performance: The Balanced Scorecard and Compensation -- Reporting Balanced Scorecard Results -- Maintaining the Balanced Scorecard -- Balanced Scorecards in the Public and Not For Profit Sectors -- External Reporting and the Balanced Scorecard -- Concluding Thoughts on Balanced Scorecard Success; Neal A. Newfield, Ph.D., LICSW (Giver)